A Case for Personal Meetings with the Federal Ethics Commissioner - Greene, Ian (The Journal of Public Policy, Administration, and Law, 2011)
Every province and territory in Canada has an independent ethics commissioner, along with ethics rules, and so too does the House of Commons, the Senate, and cabinet. The ethics regime for the House of Commons and the cabinet, however, appears to be the least successful of these ethics regimes in preventing breach of the rules. This article identifies the major weaknesses of the federal ethics regime. While in most other jurisdictions the ethics commissioner meets annually with all legislators to explain the rules, the extensive mandate of the federal ethics commissioner makes fulfilling the primary function – prevention through education – challenging. Face-to-face meetings between the ethics commissioner and members of the House of Commons and cabinet rarely occur. The author reviews inquiries made by the two House of Commons commissioners since 2004, and argues that many of the inquiries would have been unnecessary if face-to-face meetings had been held.